Theoretical Studies of Molecular Structure and Vibrational Spectra of 2-Ethyl-1H-benzo[d]imidazole - ARSLAN, HAKAN; ALGUL, OZTEKIN (Asian Journal of Chemistry, 2010)
Molecular geometry and vibrational spectra of 2-ethyl-1H-benzo[d]imidazole in the ground state has been calculate using the Hartree-Fock and density functional usin Becke's three-parameter hybrid method with the Lee, Yang and Parr correlation functional (B3LYP) methods with 6-31G(d) basis set. The computational frequencies are in good agreement with the observed results. Comparison of the observed fundamental vibrational frequencies of 2-ethyl-1Hbenzo[d]imidazole and calculated by density functional B3LYP and Hartree-Fock methods indicate that B3LYP is superior to the scaled Hartree-Fock approach for molecular vibrational spectra.